Establishment and application of a rapid molecular diagnostic platform for the isothermal visual amplification of group B Streptococcus based on recombinase polymerase - Liu, Meilin; Wang, Huan; Chu, Chu; Min, Fanli; Sun, Lizhou; Zhang, Teng; Meng, Qian (Frontiers in Cellular and Infection Microbiology, 2024)
With growing concerns about Group B Streptococcal (GBS) infections and their adverse effects on perinatal pregnancies, including infection, premature delivery, neonatal septicemia and meningitis, it is urgent to promote GBS screening at all pregnancy stages. The purpose of this study is to establish a device-independent, fast, sensitive and visual GBS detection method. Taking advantage of the characteristics of the recombinase polymerase isothermal amplification (RPA), the activity of the nfo nuclease cleavage base analog (Tetrahydrofuran, THF) site, and the advantages of visual reading of the lateral flow chromatography strip (LFS), a GBS detection method was developed. This method focused on the conservative region of the christie-atkins-munch-petersen factor encoded by the cfb gene, a virulence gene specific to GBS. Two forward primers, two biotin labeled reverse primers, and one fluorescein isothiocyanate (FITC)-labeled and C3spacer-blocked probe were designed. The study involved optimizing the primer pair and probe combination, determining the optimal reaction temperature and time, evaluating specificity, analyzing detection limits, and testing the method on 87 vaginal swabs from perinatal pregnant women. The results showed that the visual detection method of GBS-RPA-LFS, using cfb-F1/R2/P1 primer probe, could detect GBS within 15 minutes at the temperature ranging from 39°C to 42°C. Furthermore, the method specifically amplified only GBS, without cross-reacting with pathogens like Lactobacillus iners, Lactobacillus crispatus, Candida albicans, Listeria monocytogenes, Yersinia enterocolitica, Klebsiella Pneumoniae, Enterobacter cloacae, Citrobacter freundii, Vibrio alginnolyfificus, Vibrio parahaemolyticus, Salmonella typhimurium, Staphylococcus aureus, Pseudomonas aeruginosa, or Trichomonas vaginalis. It could detect a minimum of 100 copies per reaction. In clinical 98 samples of vaginal swabs from pregnant women, the agreement rate between the GBS-RPA-LFS method and TaqMan real-time fluorescence quantification method was 95.92%. In conclusion, this study successfully established a combined RPA and LFS GBS in-situ detection platform, with short reaction time, high sensitivity, high specificity, portability, and device independence, providing a feasible strategy for clinical GBS screening.